Penerapan Perhitungan Dan Pelaporan Pajak Perhotelan (Studi Kasus Di Beberapa Hotel Yang Ada Di Kota Gorontalo) - Siti Fatmawati Djafar; Hartati Tuli; Victorson Taruh (STIE AMKOP, 2023)
Study This aim For discover and find out How application calculation and reporting tax hotels in Gorontalo City are appropriate with applicable laws and mechanisms existing taxes. Study This use method qualitative with approach descriptive with use primary data sources obtained in a manner direct from observation and interview as well as outcome data documentation. Research location located at Hotel Maqna and Hotel Grand Q. The results of the research conducted show that Application calculation tax existing hospitality at Hotel Maqna and Hotel Grand Q has in accordance with rule existing taxes and regulations applicable area that is For calculation tax the hotel i.e. 10% multiplied to total hotel revenue. as well as Application reporting tax hospitality Already in accordance with system owned by each - each hotel. Keywords : Hotel Tax, Application Calculations, Reporting